E-3: PAK-CHINA COOPERATION IN SOCIO-ECONOMIC DEVELOPMENT OF THE REGION - Akhtar, Sohail; Khan, Mamnoon Ahmed; Jabeen, Rizwana (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
This research paper mainly studies and explores the bilateral relations between Pakistan and China. Pakistan and China became independent shortly after World War II. When China became independent, Pakistan immediately recognized China and the reason for this immediate action was the development of bilateral relations and the threat posed by India to both in the region. The full military support of Russia and the United States was of great importance to India, thanks to which India began to gain power in the region and a bipartisan relationship was necessary to deal with its aggression. Tensions with India not only helped to bring Pakistan and China closer, but also quickly resolved border disputes. While the Soviet threat and the dual policy of the United States brought Pakistan closer to China, Pakistan acted as a bridge between China and the West to improve their relations. In the same way, the race for the regional leadership, Pakistan helped China against the global conspiracies. Similarly, China assisted in meeting the defense and economic needs of Pakistan and created a challenge for India by launching various trade and economic projects. One of which is the trade freight scheme. This is a possible plan for China's supremacy in the region's economic balance, and the United States, including India, fears it. Pak-China relations have been boosted in view of these common threats due to US intervention through India and then India's policy of annihilation of Pakistan to prevent this from happening. Even in the race for power, China needs Pakistan's close cooperation so that it can reach the global market. Therefore, a common enemy, India, has brought these two countries closer to each other in bilateral relations.